Exploring Students’ Cognitive Presence in AI-Assisted Learning Environments: A Qualitative Inquiry in Higher Education - Mayasari, Mayasari; Agus Purwanto; Agustinus Prasetyo Edy Wibowo; Syamsudin (PT FORMOSA CENDEKIA GLOBAL, 2026)
The integration of artificial intelligence (AI) in higher education reshapes the learning process by positioning AI as a learning partner that influences students’ thinking, information exploration, and academic decision-making. This qualitative case study explores students’ cognitive presence in AI-assisted learning using the Community of Inquiry framework, focusing on the phases of triggering, exploration, integration, and resolution. Data were collected through semi-structured interviews, observations of digital learning activities, and analysis of student interactions on an AI platform involving 12 students from a technology-based university in Gading Serpong. The findings show that AI effectively supports the triggering and exploration phases through adaptive feedback and conceptual assistance, while knowledge integration relies largely on students’ self-reflection. The resolution phase emerges primarily among students with higher digital literacy and self-regulation. The study concludes that AI can enhance cognitive presence, but its impact depends on students’ cognitive readiness and instructional design, contributing to AI-based learning theory and informing more adaptive, student-centered learning environments.